2011
DOI: 10.2202/1553-3840.1533
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycaemic And Renoprotective Effect of Boerhaavia diffusa L. in Experimental Diabetic Rats

Abstract: The present study evaluates the efficacy of ethanolic extract of Boerhaavia diffusa L (BD) administered orally at a dose of 500mg/kg body weight for a period of 30 days to alloxanized diabetic rats and its efficacy compared with the standard hypoglycaemic drug metformin. Diabetic animals showed glycemic dysregulation, altered ionic balance, increased levels of serum markers of kidney function, and reduced Na+-K+ ATPase activity and endogenous antioxidant status. Administration of BD not only maintained the ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Oral administration of aqueous extract of O. sanctum (O. tenuiflorum) mixed with diet for 8 weeks showed a significant reduction in fasting blood glucose, lipid peroxidation products, serum lipid profile and improvement in glucose tolerance (Hussain et al 2001). In a study carried out by Hannan et al 2006, ethanol, butanol Anti-diabetic Pari and Satheesh (2004) and Singh et al (2011) 15 Ankolekar et al (2011) and Abeywickrama et al (2011) and Satoh et al (2015) 19 Bavarva and Narasimhacharya (2008) and Eliza et al (2009) 27 Curcuma longa Hypoglycemic, antidyslipidemic Sachdewa and Khemani (2003) and Kumar et al (2013) 37 Ipomoea batatas Anti-hyperglycemic, antihyperlipidemic Deguchi and Miyazaki (2010) and Huang et al (2011) 56 Arul et al (2004) and Khan et al (2013) Xue et al (2007) and Kumar et al (2012) 67 Urtica dioica antioxidant effects in cholesterol-fed rabbits (Gupta et al 2006).…”
Section: Ocimum Tenuiflorum L (Holy Basil)mentioning
confidence: 99%
“…Oral administration of aqueous extract of O. sanctum (O. tenuiflorum) mixed with diet for 8 weeks showed a significant reduction in fasting blood glucose, lipid peroxidation products, serum lipid profile and improvement in glucose tolerance (Hussain et al 2001). In a study carried out by Hannan et al 2006, ethanol, butanol Anti-diabetic Pari and Satheesh (2004) and Singh et al (2011) 15 Ankolekar et al (2011) and Abeywickrama et al (2011) and Satoh et al (2015) 19 Bavarva and Narasimhacharya (2008) and Eliza et al (2009) 27 Curcuma longa Hypoglycemic, antidyslipidemic Sachdewa and Khemani (2003) and Kumar et al (2013) 37 Ipomoea batatas Anti-hyperglycemic, antihyperlipidemic Deguchi and Miyazaki (2010) and Huang et al (2011) 56 Arul et al (2004) and Khan et al (2013) Xue et al (2007) and Kumar et al (2012) 67 Urtica dioica antioxidant effects in cholesterol-fed rabbits (Gupta et al 2006).…”
Section: Ocimum Tenuiflorum L (Holy Basil)mentioning
confidence: 99%
“…integrin-linked kinase, EMT, MMP-9/TIMP-1 ratio [127] ( 10 Journal of Diabetes Research 12 Journal of Diabetes Research ↓: decreased/prevented the increase (of activity (for enzymes)/level (for biochemical parameters))/inhibited/inactivated/blocked/suppressed/downregulated (about pathways, enzymes, receptors, cytokines, etc. ); ↑: increased/prevented the decrease (of activity (for enzymes)/level (for biochemical parameters))/stimulated/activated/upregulated; →: [172], Chlorella pyrenoidosa [173], Cladophora glomerata [34], Coccinia indica [111], coconut water [61], Cordyceps militaris [114], Cornus officinalis [47], curcumin [79], dihydroquercetin [48], Dioscorea bulbifera [96], diosgenin [62], ellagic acid [37], emodin § [94], Flammulina velutipes [53], Fragaria × ananassa [89], Huangqi decoction [36], Hypericum perforatum [31], Paederia foetida [78], Paeonia emodi [63], palm oil and rice bran oil [50], Panax notoginseng [35], Panax quinquefolium [82], Panax quinquefolium [83], Physalis angulata [64], Pleurotus eryngii polysaccharides [57], Prunella vulgaris [84], Punica granatum [32], quercetin [49], Ramulus mori [77], Rheum ribes [175], secoisolariciresinol diglucoside [88], Spirogyra neglecta [176], Tangke decoction [116], Terminalia chebula [33] Insulin resistance…”
Section: In Vitro Studies-potentially Nephroprotectivementioning
confidence: 99%
“…Continued. Boerhaavia diffusa[172], breviscapine[51], Coccinia indica[111], coconut water[61], curcumin[108], d-pinitol[2], ellagic acid[37],…”
mentioning
confidence: 99%
“…Pharmacological studies have reported in Boerhaavia diffusa as anticonvulsant [12], cardioprotective [13], anti-inflammatory [14], antidiabetic [15], anti-arthritic [16], hepatoprotective [17], anxiolytic activity.18…”
Section: Introductionmentioning
confidence: 99%